MATHEMATIC MODEL FOR SITY BUS SCHEDULING IN YOGYAKARTA - Sahid Sahid; Fitriana Yuli S; Dwi Lestari (Faculty of Mathematics and Natural Science, Universitas Negeri Yogyakarta, 2015)
Various methods can be used to construct a mathematical model of the transportation problems. One model that can be used is a linear model. Several studies have used a linear model to get the schedule and the optimal route of bus trips. This research will build a mathematical model of a city bus transportation problems in DIY using linear models. Linear model is built to get the condition density city bus passengers on shifts respectively that morning, noon, and evening. After finding a suitable model, applied to the bus passengers data in Yogyakarta. From these results it can be seen the optimum conditions in terms of density, because the condition of the city bus at this time that quiet enthusiasts. Besides, the optimum density at each shift in the morning is 11 passengers, 10 passengers during the day, and evening 9 passengers. Keywords: transportation problems, the linear model, the optimal route, density